Studying the influence of organizations as a city model based on the changes of user change in zone 6 of tehran - alireza vousoghi amiri; rojin marzi; mahsa bashtam; kiarash pourhazhir ardestani; seyedeh sepideh ghalamro (تحقیقات کاربردی علوم جغرافیایی)
the aim of this study is to explain the impacts and impacts of organizations such as municipality on land use management in the tehran metropolitan area to determine and change land use patterns in documents and factors affecting them . because of the qualitative research approach and its type , the influence of organ and document content including land use projects in tehran was used . research findings show that land use management in tehran with conflicts in land use management , weakness in land use management , weakness in land use management system , weakness in land use management system , weakness in land use management system , weakness factor in land use management system , weakness factor in land use management system , informal and quasi - governmental agent and private agent are classified . finally , the change of land use change in tehran metropolitan area has been studied and challenges and opportunities are presented . the research method is analytical and by software soft ware and t - test .